Building siRNAs with Cubes: Synthesis and Evaluation of Cubane‐Modified siRNAs. (11th August 2021) - Hammill, Matthew L.; Salim, Lidya; Tsubaki, Kouta; Varley, Andrew J.; Kitamura, Mitsuru; Okauchi, Tatsuo; Desaulniers, Jean‐Paul
Abstract: Cubane molecules hold great potential for medicinal chemistry applications due to their inherent stability and low toxicity. In this study, we report the synthesis of a cubane derivative phosphoramidite for the incorporation of cubane into small interfering RNAs (siRNAs). Synthetic siRNAs rely on chemical modifications to improve their pharmacokinetic profiles. However, they are still able to mediate sequence‐specific gene silencing via the endogenous RNA interference pathway. We designed a library of siRNAs bearing cubane at different positions within the sense and antisense strands. All siRNAs showed excellent gene‐silencing activity, with IC50 values ranging from 45.4 to 305 pM. Incorporating the cubane modification in both the sense and antisense strand led to viable duplexes with good biological activity. To the best of our knowledge, this is the first report of siRNAs bearing a cubane derivative within the backbone. Abstract : siRNA lego : Cubane‐functionalized siRNAs lead to potent RNAi‐mediated gene‐silencing activity, and improved strand selection.